Quality and alpha-glucosidase inhibitory activity of fresh-cut pineapple coated with Neptunia oleracea Lour. and Cosmos candatus Kunth. leaf extracts - Yong, Yeng Yeng (2021)
The MD2 pineapple (Ananas comosus) is highly demanded in Malaysia due to its sweet taste and refreshing smell. Wounding of fruit tissues during cutting shortens the shelf life of cut fruits as they are susceptible to deterioration. Besides, taking a large serving size of fresh-cut MD2 pineapple will result in a spike of blood sugar level for diabetic patients. This study aimed to evaluate the storage stability and alpha-glucosidase inhibitory activity of fresh-cut MD2 pineapple coated with an edible coating which was incorporated with either water mimosa (Neptunia oleracea Lour.) or Ulam Raja (Cosmos caudatus Kunth.) leaf extract. Two types of edible coating were compared in this study, namely Aloe vera gel and alginate-based coating. Aloe vera gel coating was more effective on retaining the storage stability of fresh-cut MD2 pineapple by maintaining microbiological quality up to 14 days with reduced fluid loss. The water mimosa and Ulam Raja leaf extract coating formulation on fresh-cut MD2 pineapple was optimized by response surface methodology (RSM). The optimised water mimosa leaf extract coating formulation was 71.72% (w/v) Aloe vera gel and 1.62% (w/v) water mimosa leaf extract while and the optimised Ulam Raja leaf extract coating formulation was 20% (w/v) Aloe vera gel and 1.59% (w/v) Ulam Raja leaf extract. There was no significant (p ˃ 0.05) difference between the samples coated with the optimised coating formulation and uncoated samples in term of colour, aroma, taste, texture and the overall acceptability under sensory evaluation. The coated MD2 pineapples were further evaluated for total phenolic content (TPC), DPPH free radical scavenging, alphaglucosidase inhibitory activity, physicochemical and microbiological properties. Results showed that coated samples with the extracts incorporated have a significantly (p ˂ 0.05) higher value of TPC, DPPH free radical scavenging and alpha-glucosidase inhibitory activity than uncoated samples and samples coated with Aloe vera alone. The extract- coated samples also displayed a significant (p ˂ 0.05) reduced fluid loss, better retention in pH value and total soluble solid and had longer shelf life extension compared to uncoated samples. In conclusion, incorporation of water mimosa and Ulam Raja leaf extract on Aloe vera coated fresh-cut pineapple has the potential to enhance the functional value of fresh-cut pineapples and extend the shelf life up to 8 days, without compromising the physiochemical quality during storage at 5±1 oC.